Aroma components analysis of 'Marselan' dry red and rose wines in different producing areas - CHEN Jiawei, QIN Yanfei, SUN Jianping (Zhongguo niangzao)
The volatile flavor components of 'Marselan' dry red and rose wines from Shacheng and Changli producing areas were analyzed by headspace solid-phase microextraction (HS-SPME)-gas chromatography-mass spectrometry (GC-MS), the key aroma substances of the wine samples were analyzed with odor activity value (OAV), and principal component analysis (PCA) based on the test results was carried out. The results showed that a total of 50 volatile flavor components were identified in the dry red wines from both producing areas, 47 and 49 kinds of volatile flavor components and 22 key aroma components（OAV>1） were detected in rose wine from Shacheng and Changli, respectively. The contents of volatile flavor components in rose and dry red wines from Shacheng producing area (0.74g /L and 1.46g /L) were higher than those in Changli producing area (0.59 g/L and 1.00 g/L), respectively. There were obvious differences in aroma profiles between 'Marselan' dry red and rose wines. The fruit aroma and cheese aroma of rose wine were prominent, and the contribution of linear fatty acid ethyl ester, fatty acid and isoamyl acetate was significant. Fruity, floral and mellow flavor of dry red wines were prominent, and the contribution of branched-chain fatty acid ethyl ester, β-ionone, 2-phenylethanol and higher alcohol was significant. Changli 'Matheran' dry red wines had significant floral aroma, and the contribution of phenylethanol, phenylacetaldehyde and β-ionone was significant. Shacheng 'Matheran' dry red wines had obvious mellow, plant aroma, and the contribution of 2,3-butanediol, 1-hexanol was significant. PCA could distinguish wine samples with different producing areas.